Integrated Management of Physician-delivered Alcohol Care for Tuberculosis Patients: Design and Implementation - Greenfield, Shelly F.; Shields, Alan; Connery, Hilary Smith; Livchits, Viktoriya; Yanov, Sergey A.; Lastimoso, Charmaine S.; Strelis, Aivar K.; Mishustin, Sergey P.; Fitzmaurice, Garrett; Mathew, Trini A.; Shin, Sonya (Alcoholism, clinical and experimental research, 2010)
Background:  While the integration of alcohol screening, treatment, and referral in primary care and other medical settings in the U.S. and worldwide has been recognized as a key health care priority, it is not routinely done. In spite of the high co‐occurrence and excess mortality associated with alcohol use disorders (AUDs) among individuals with tuberculosis (TB), there are no studies evaluating effectiveness of integrating alcohol care into routine treatment for this disorder. Methods:  We designed and implemented a randomized controlled trial (RCT) to determine the effectiveness of integrating pharmacotherapy and behavioral treatments for AUDs into routine medical care for TB in the Tomsk Oblast Tuberculosis Service (TOTBS) in Tomsk, Russia. Eligible patients are diagnosed with alcohol abuse or dependence, are newly diagnosed with TB, and initiating treatment in the TOTBS with Directly Observed Therapy‐Short Course (DOTS) for TB. Utilizing a factorial design, the Integrated Management of Physician‐delivered Alcohol Care for Tuberculosis Patients (IMPACT) study randomizes eligible patients who sign informed consent into 1 of 4 study arms: (1) Oral Naltrexone + Brief Behavioral Compliance Enhancement Therapy (BBCET) + treatment as usual (TAU), (2) Brief Counseling Intervention (BCI) + TAU, (3) Naltrexone + BBCET + BCI + TAU, or (4) TAU alone. Results:  Utilizing an iterative, collaborative approach, a multi‐disciplinary U.S. and Russian team has implemented a model of alcohol management that is culturally appropriate to the patient and TB physician community in Russia. Implementation to date has achieved the integration of routine alcohol screening into TB care in Tomsk; an ethnographic assessment of knowledge, attitudes, and practices of AUD management among TB physicians in Tomsk; translation and cultural adaptation of the BCI to Russia and the TB setting; and training and certification of TB physicians to deliver oral naltrexone and brief counseling interventions for alcohol abuse and dependence as part of routine TB care. The study is successfully enrolling eligible subjects in the RCT to evaluate the relationship of integrating effective pharmacotherapy and brief behavioral intervention on TB and alcohol outcomes, as well as reduction in HIV risk behaviors. Conclusions:  The IMPACT study utilizes an innovative approach to adapt 2 effective therapies for treatment of alcohol use disorders to the TB clinical services setting in the Tomsk Oblast, Siberia, Russia, and to train TB physicians to deliver state of the art alcohol pharmacotherapy and behavioral treatments as an integrated part of routine TB care. The proposed treatment strategy could be applied elsewhere in Russia and in other settings where TB control is jeopardized by AUDs. If demonstrated to be effective, this model of integrating alcohol interventions into routine TB care has the potential for expanded applicability to other chronic co‐occurring infectious and other medical conditions seen in medical care settings.